PERÚ EN EL NIVEL DE GRADO DE INVERSIÓN - Mayurí Barrón, Jorge Vicente (2008)
The credit rating agency Fitch Ratings gave Peru on Wednesday, April 2, 2008, the first step in the group ratings for the so-called investment grade, by raising the qualification of the Peruvian longterm debt in foreign currency “BB +” (speculative grade) to “BBB-” with positive outlook, also raised the rating of the debt in local currency long-term “BBB-” to “BBB”, also with a stable outlook, and that was already under the classification of investment grade. This attribute what will bring tangible benefits for the country’s economy? ¿can improve the per capita income of peruvians? ¿do encourage the creation of new jobs? ¿can reduce the level of poverty in the country? ¿why just Mexico, Chile and Peru are now the only countries that have reached this category? In the next lines, we will try to respond to each and every one of the questions raised.